True phosphorus absorption from different sources for sheep, using radiophosphorus (P-32) - Vitti, Dorinha Miriam Silber Schmidt; Abdalla, Adibe Luiz; Meirelles, Cyro ferreira; Filho, José Cleto da Silva; Louvandini, Helder (Pesquisa Agropecuaria Brasileira, 1992)
A serie of experiments with sheep was carried out to determine the endogenous fecal loss and the true P absorption. Male sheep were kept in metabolic cages in a semipurified diet, and P sources were added to give 4 g of P/head/day. The sources tested were: dicalcium phosphate (BIC), bone meal (FO), monoammonium phosphate (MAP), superphosphate (SP), acidulated phosphate (AC), Patos rock phosphate (PAT) and Tapira phosphate (TAP). After 15 days, 200 mCI of P-32 were intravenously injected and blood and feces samples collected during eight days. Fecal losses and absorption coefficient were determined. In relation to total P in feces, endogenous P values were in 20% mean for rock phosphates and 45% for the other sources. Absorption coefficient values were 0,62; 0,67; 0,59; 0,42; 0,43; 0,70 and 0,44 respectively for BIC, FO, MAP, AC, PAT, SP and TAP.